Cutaneous squamous cell carcinomas with markers of increased metastatic risk are associated with elevated numbers of neutrophils and/or granulocytic myeloid derived suppressor cells. Issue 2 (August 2016) - Seddon, Annika; Hock, Barry; Miller, Andrew; Frei, Lukas; Pearson, John; McKenzie, Judith; Simcock, Jeremy; Currie, Margaret
Highlights: High circulating neutrophil counts are associated with known features of high-risk CSCC and poor overall survival in immunocompetent patients. Increased tumor thickness is associated with increased peritumoural and tumor-localised neutrophils. The function and prognostic value of neutrophils in CSCC merits further investigation. Abstract: Background: A subset of presenting cutaneous squamous cell carcinomas (CSCC) is high risk with respect to their high rates of recurrence, metastasis and patient death. The identification of such high risk CSCC is problematic. Neutrophil and granulocytic myeloid derived suppressor cell (G-MDSC) numbers are elevated in a number of cancers, but their association with current markers of high risk tumors in the setting of CSCC is unknown. Objectives: To assess circulating and tumor-localised neutrophil and G-MDSC populations for associations with high-risk tumor characteristics and overall survival (OS) in CSCC patients. Methods: A retrospective clinical audit was performed of patients who had hospital operations for primary CSCC and did not have other malignancies or HIV. Therapeutically immuno-suppressed individuals (TII, n = 129) and non-TII (n = 29) were analysed separately with respect to the presence of high-risk tumor features and OS. In addition, 47 patients with prospectively collected blood and primary CSCC tumor samples were analysed to determine frequencies of circulating G-MDSC and tumor localised CD66b+ and CD8+ leukocytes. Results: In the clinical audit of non-TII, high circulating neutrophil counts were associated with tumor thickness ≥ 5 mm, Clark level V and high T-stage. Univariate analysis showed elevated neutrophil count was a significant marker of poor OS, whilst tumor thickness remained the only independent histological predictor of OS after adjusting for age and immuno-suppression. The prospective study demonstrated that tumors ≥ 5 mm thick had significantly increased total and peri-tumorally localised CD66b+ leukocytes (comprising neutrophils and/or G-MDSC) and that elevated circulating G-MDSC numbers were associated with high T-stage tumors. Conclusions: This study demonstrates that the presence of high risk CSCC is associated with increased numbers of both circulating and tumor resident populations of neutrophils and/or G-MDSC. These cell types therefore merit further investigation with respect to their functional and prognostic significance in CSCC.